Testing the Theory of Tournaments: An Empirical Analysis of Broiler Production - Knoeber, Charles R.; Thurman, Walter N. (Journal of Labor Economics, 1994)
Broiler chickens are raised by contract growers whose rewards depend explicitly upon relative performance. The authors use data on the performance of broiler producers facing both tournament and linear performance evaluation compensation structures to test three predictions from the theory of tournaments: that changes in the level of prizes that leave prize differentials unchanged will not affect performance; that, in mixed tournaments, more able players will choose less risky strategies; and that tournament organizers will attempt to handicap players of unequal ability or reduce mixing to avoid the disincentive effects of mixed tournaments. Their evidence is consistent with each prediction. Copyright 1994 by University of Chicago Press.